The public/private relationship in special education policies during the dictatorship period in Brazil (1964-1985) - Bueno, José Geraldo Silveira; Lehmkhul, Márcia de Souza; Goes, Ricardo Schers de (Education Policy Analysis Archives, 2019)
This article aims to analyze the relationship between the public and private instances in special education policies in Brazil during the period of the civil-military dictatorship (1964/1985). Despite the advances private-philanthropic institutions of special education had obtained in the previous period (1945 to 1963), it was during the dictatorship that institutions specializing in special education received incentives that allowed their dissemination throughout the Brazil. It was also during this period that they increased their influence over national policies for special education. Through document analysis, we were able to detail and analyze scarcely known processes of this relationship, involving public funding granted to these institutions and the political influence they exerted during that time.